Modelling optimize of searching student’s information in Souphanouvong University by using Bitmap and B-tree index methods - SOUKCHALEUN, Xaysavath; MEKTHANAVANH, Vinath; MANIVANH, Vialakhone; yang, Xang; KHONGKET, Thongphet (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Currently, there are many types of data used in the database system. Database is an important for the organization's data collection. It is a centralization of the organization for using in various work by implementing different techniques to search information from database. Different techniques, the time for processing is different. In this paper, we increased the effectiveness of searching student information of Souphanouvong University by using Bitmap index and B-tree index. “After that” we compared the results between the technique of with and without using indexes. In the experiment, we used three attributes of student information there are scores, registration, and subjects. Experimental results show that the time using in both types of indexes outperformed simple technique.